AKUNTABILITAS PENGELOLAAN ANGGARAN DANA DESA DALAM PEMBANGUNAN INFRASTRUKTURDI DESA KOKOLEH SATU KECAMATAN LIKUPANG SELATAN - Ngongare, Yanis; Mantiri, Michael Stepanus; Kairupan, Josef (JURNAL EKSEKUTIF, 2016)
AbstractThis research focus towards forms and systems of accountability the management and utilization of village Fund in infrastructure development in the village of Kokoleh I (one) by 2015. Accountability is referred to as accountability, presenting, reporting, and reveal all activities and activities be the success or failure of a program and is the responsibility of the Government to the public. This research was conducted to find out the third stage planning, implementation, and accountability for the management of funds of the village in the village of Kokoleh I (one). This research is supported by the existence of technical supervision, operation and evaluation of the team Escort Subdistrict, BPD in order to prove the existence of the application of accountability and transparent in the management of the village Fund in the village of Kokoleh I (one). Data collection is done by the method of observation and interviews. As the informant this research there are 10 respondents village chief 1 person, Chairman of BPD is community leaders, community 3 people, Youth Figure one person. This research is descriptive research with qualitative approach. The results of this research show that the planning stages, execution and accountability for the management of funds in the village infrastructure development in the village of Kokoleh I has not applied the principle of accountable with indicators of honesty and law, processes, programs and policies which are still not in accordance with the applicable guidelines.Key word : the village fund management, accountability, and development